Thermal power plant control and instrumentation : the control of boilers and HRSG systems - Lindsley, David, 1937-; Grist, John; Parker, Don (IET energy engineering series, 2018)
Power-plant Control and Instrumentation, 2nd edition - contents include a wide variety of plant and combustion arrangements, from smaller boiler systems to full-scale generators, common principles, commercial aspects, measurement, and key techniques such as cogeneration and combined cycle.